Elective neck dissection versus observation for early-stage oral squamous cell carcinoma: Systematic review and meta-analysis. (June 2020) - Oh, L.J.; Phan, K.; Kim, S.W.; Low, T.H.; Gupta, R.; Clark, J.R.
Highlights: We compared elective neck dissection (END) to observation for early-stage tongue SCC. END was associated with significantly lower recurrence rates. END was associated with higher overall and disease-specific survival. Abstract: Introduction: Oral squamous cell carcinoma (OSCC) is the seventh most common cancer globally, and has been identified as a growing health concern. This study aims to evaluate the current literature comparing elective neck dissection to observation in the treatment of early-stage tongue SCC, focusing on nodal recurrence, overall survival, disease specific survival statistics from randomised controlled trials comparing the two interventions. Methods: Systematic review and meta-analysis was conducted according to PRISMA guidelines. The odds ratio (OR) was used as a summary statistic. Results: From 8 studies, there was a total of 372 cases of recurrence, 98 (15.1%) in END group and 274 (41.5%) in the Observation group. There was a significantly lower rate of recurrence in the END group compared to observation (OR 0.25, 95% CI 0.16–0.39, I 2  = 54%, P < 0.00001). END was associated with higher overall survival rates when compared with observation (OR 1.95, 95% CI 1.40–2.73, I 2  = 14%, P < 0.0001). END was also associated with higher disease-specific survival compared with observation (OR 1.88, 95% CI 1.21–2.93), I 2  = 47%, P = 0.005), with no significant heterogeneity noted. Conclusions: END was associated with significantly lower recurrence rates and higher overall and disease-specific survival compared to a conservative observation approach in early-stage oral SCC with clinically N0 neck.